Brand new baby - Graham, Bob (London : Walker Books, 2014)
Mum is having a baby, but when it arrives Wendy and Edmund aren't too sure about having a new baby in the family. After all it doesn't do anything, except take up Mum and Dad's time.
Keywords: Children's stories